Prognosis and biology in esthesioneuroblastoma: the emerging role of Hyams grading system - Saade, Rami E. (2015)
Esthesioneuroblastoma is a sinonasal tumor with distinct clinicopathologic features, multiple facets, and a spectrum of behavior. Characterization of this disease is challenging, and clinically, several staging systems have been used with no consensus on a single scheme. Recently, the Hyams histological grading system has emerged as a promising prognostication tool that offers an added value to stage. This review addresses prognosis and biology in esthesioneuroblastoma. More specifically, we sought to present a critical appraisal on the value of each of these stratification systems, stage vs. grade, in identifying risk groups and guiding management.